Comparative evaluation of adherence to antiretroviral therapy - Singla, Ritika; Sharma, Neetu (International Journal of Basic & Clinical Pharmacology, 2019)
Background: While treating patients with HIV infection it is important to achieve more than 95% compliance to ART (Antiretroviral Therapy) in order to suppress viral replication. Methods: This was a retrospective, observational, record based study of HIV positive patients undergoing treatment with ZLN (zidovudine 300 mg, lamivudine 150 mg, nevirapine 200 mg) and TLE ( tenofovir 300 mg, lamivudine 150 mg, efavirenz 600 mg) regimens. The treatment charts of the patients fulfilling inclusion and exclusion criteria were reviewed. Results: Analysis of adherence showed that there were 12 patients out of 150 on ZLN regimen and 31 patients out of 150 on TLE regimen were nonadherent to the respective treatments. Conclusions: In this observational study patients on ZLN regimen were showing greater compliance than TLE regimen.